Dancing / Listening Book / CD review - Still, Jonathan (Dance Books Ltd., Alton,Hampshire (UK), 2004)
PALABRAS CLAVE: contemporary dance, dance photographers, Jocelyn Pook, Michael Nyman.
Dentro del apartado "Shelf Content".
Danding / Listening. CD/Journal No: UP15, Unknoen Public, 2004.